Enhanced dielectric properties of immiscible poly (vinylidene fluoride)/low density polyethylene blends by inducing multilayered and orientated structures. (1st April 2017) - Lin, Xiang; Fan, Lili; Ren, Dongyun; Jiao, Zhiwei; Coates, Phil; Yang, Weimin
Abstract: In order to improve the frequency-dependent dielectric properties of the immiscible polymeric blends which were melt-compounded by composing poly (vinylidene fluoride) (PVDF) and low density polyethylene (LDPE), the layer multiplication and the solid phase orientation technologies were respectively adopted as two effective strategies to optimize the dispersion state and the orientation of internal microstructure, aiming at reducing physical porosity and improving the barrier performance as well as crystal phase of the polymer extrudates. Results comparison showed the dielectric properties were greatly dependent on the crystal type and the physical porosity density which were also emphasized as the interfacial effect in the previous work [ ref. 29: Lin X et al., J Appl Polym Sci 2015; 132(36), 42507 ]. It was found that the multilayer-structure manipulation could substantially improve the dispersion state between the two immiscible components, enhance the mechanical performance and reduce the internal defects and increase the dielectric constant while keeping the dielectric loss stable. By uniaxial stretching the sample sheets at a rubber state temperature of ca. 10–20 °C below the melting point, crystal transformation was induced by increasing molecular chains orientation degree which was also contributed to the enhancement of the dielectric properties. These techniques implied the potential as a promising way for inducing functional structures of polymeric blends.